Gender differences for growth in North American Atlantic salmon. (7th March 2018) - Schaeffer, L.; Tosh, J. J.; Ang, K.P.; Elliott, J.A.K.; Herlin, M.; Powell, F.; Boulding, E. G.
Summary: An assumption in aquaculture of Atlantic salmon is that male and female growth within families is perfectly genetically correlated. That is, families would rank identically if based on male growth only or female growth only. Also, growth in freshwater and sea water is assumed to be highly correlated between males and females within families. However, structural analysis of the DNA of Atlantic salmon has found that the linkage maps of females differ significantly from that of males. Genetic variability for any trait measured on females could be greater or lesser than on males. Thus, male and female growth might be considered as separate traits giving rise to families ranking differently depending on gender. A multiple trait family model for weight and length at 3 years of age in Atlantic salmon according to gender was applied to data on North American Atlantic salmon obtained from the Oak Bay Hatchery in New Brunswick, Canada. Genetic correlations between male and female growth in both freshwater and sea water were estimated by Bayesian methods. The estimates support the possible existence of gender dimorphism in North American Atlantic salmon for growth traits.